Sociological perspectives regarding the effects in tourism in the southern area of the Romanian coast, considering the sociological and economical changes of the area: Olimp Resort - Oprescu, Georgiana (Technium Social Sciences Journal, 2021)
The article is an analysis of the Phoenician tourism concept in the South of the Romanian coast, respectively the parallel generation-gentrification given the changes that have taken place over the years, with different generational, political, and social imprints and last but not least with different economic imprint over time. Thus, the zonal social elements, respectively the inhabitants and investors, participated directly and indirectly in the evolution and involution of the area and that of tourism. Currently, the area enjoys a social, touristic, and economic rise, and the main factor is the influence given by the development and rebirth of zonal tourism as an effect of the Romanian Phoenician tourism concept. The present study highlights the connection between tourism, the gentrification of Olimp Resort, and the imprint of generations in the reconstruction of a current social episteme.